(untitled) (Damascus University Journal for engineering sciences, 2024)
Sculpture Art is historically known as that field of art in which the sculptor uses solid materials for expression. These materials are usually opaque, reflecting the falling light to form shadows behind them that emphasize the weight and stability of the material. Wood, stones, and even metals and scrap in the modern stages are opaque materials that the sculptor deals with by cutting or building to form the artwork. At the beginning of the twentieth century, some artists’ experiences turned to research the properties of transparent materials and their uses in their artistic presentation. Some sculptural works made of transparent materials appeared on the art scene, most of which were of recent origin at that time. No doubt that this shift in thinking occurred in conjunction with the technical and industrial development in which Europe lived after the Industrial Revolution, and the evidence for this is that industrial materials such as plastics were the main component of these technical experiments. Materials such as celluloid, polyester, and even nylon threads have appeared in several experiments in modern sculpture. However, transparent acrylic was the most present when talking about transparency. The research sheds light on the element of transparency and its impact on modern sculpture. It also aims to highlight the plastic and functional characteristics of the transparent acrylic material that is considered appealing to sculptors who use it to add the element of transparency to their artwork.